Supply Chain Management: After Business Process Re-Engineering - Wan Mahmood, Wan Hasrulnizzam; Muhamad, Mohd Razali; Mat Tahar, Nurulain (2009)

(untitled)
This paper is prepared to provide a review of how an automotive manufacturer, ISUZU HICOM Malaysia Co. Ltd. sustained the supply chain management after business process re-engineering in 2007. One of the authors is currently undergoing industrial attachment and has spent almost 6 months researching in the production and operation management system of the company. This study was carried out as part of the tasks in the attachment program. The result shows that delivery lateness and outsourcing are the main barriers that affected productivity. From the gap analysis, the authors found that new business process operation had improved suppliers delivery performance.